2012
DOI: 10.1039/c1cp22555c
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of germanium from supercritical fluids

Abstract: Several Ge(II) and Ge(IV) compounds were investigated as possible reagents for the electrodeposition of Ge from liquid CH(3)CN and CH(2)F(2) and supercritical CO(2) containing as a co-solvent CH(3)CN (scCO(2)) and supercritical CH(2)F(2) (scCH(2)F(2)). For Ge(II) reagents the most promising results were obtained using [NBu(n)(4)][GeCl(3)]. However the reproducibility was poor and the reduction currents were significantly less than the estimated mass transport limited values. Deposition of Ge containing films w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 54 publications
(79 reference statements)
0
51
0
Order By: Relevance
“…25 In 2012 Ke et al reported the first electrodeposition of germanium thin films from a supercritical fluid. 26 Here, the observed electrochemistry was complex, in contrast to the metal systems studied previously, due to the irreversible reduction of the germanium complexes, slow electron transfer processes and the possible formation of an insulating layer. This study was on the reduction of GeCl 4 in sc-CH 2 − anion was the most readily reduced of the chloride based precursors.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…25 In 2012 Ke et al reported the first electrodeposition of germanium thin films from a supercritical fluid. 26 Here, the observed electrochemistry was complex, in contrast to the metal systems studied previously, due to the irreversible reduction of the germanium complexes, slow electron transfer processes and the possible formation of an insulating layer. This study was on the reduction of GeCl 4 in sc-CH 2 − anion was the most readily reduced of the chloride based precursors.…”
mentioning
confidence: 68%
“…Compared to our earlier work using GeCl 4(l) to electrodeposit germanium from sc-CH 2 F 2 , 26 [N n Bu 4 ][GeCl 3 ] is much easier to handle and gives more reproducible and better quality films.…”
Section: Discussionmentioning
confidence: 99%
“…These works showed that despite being possible to electrodeposit germanium from ionic liquids, there were several issues: the germanium sources are poorly soluble in the ionic liquids, non-standard experimental setups had to be used to cope with the volatility of the most common germanium compounds and deposition rates are low under standard conditions. In another approach, Bartlett et al electrodeposited amorphous germanium from liquid CH 3 [20,21]. Albeit successful, this approach presents some drawbacks: on the one hand, the need of a high pressure cell, which increases the complexity of the experiment and decreases output.…”
Section: Introductionmentioning
confidence: 99%
“…36,[41][42][43][44][45][46] Ge electroplating has also been reported on semiconducting substrates such as Si. 47 There are some reports on the formation of thick Ge nanostructures, [48][49][50] which showed that, depending on potential, Ge nanostructures can be grown from aqueous solution by dissolution into and saturation of a liquid Hg electrode.…”
mentioning
confidence: 99%
“…44 Bartlett et al have studied electrodeposition of Ge from various supercritical fluids containing Ge(II) or Ge(IV) compounds. 46 They were able to obtain amorphous Ge films from Ge(IV) and Ge(II) precursors; however, films grown from Ge(II) compounds were heavily contaminated.…”
mentioning
confidence: 99%